COVID-19: What Should We Know? - Dinda, Amit Kumar (SCHOOL SCIENCE, 2020)
The Coronavirus Disease 2019 (COVID-19) following its first outbreak in Wuhan, China has rapidly spread all over the globe as a pandemic with unprecedented morbidity and mortality. Majority of this explosive spread have occurred by human to human transmission through aerosol route with a minor element of transmission through contaminated surfaces. This brief review article describes in a simplified manner the basic understanding about the virus, the pathobiology of infection, modes of transmission and preventive measures to avoid the infection.